Populist radical left parties in Western Europe - Damiani, Marco (Routledge, Taylor & Francis Group, 2020)
Conceptual framework -- Left-wing Populism -- New identitarian approach -- Forerunners of Populism -- Ideal-typical Populism -- Populism of government -- Presidential Populism -- Others leftist Populisms -- Inside. Internal dimension -- Outside. External dimension.